Traceable and undeniable ciphertext-policy attribute-based encryption for cloud storage service - Gang Yu; Yongjuan Wang; Zhenfu Cao; Jian Lin; Xiangyu Wang (International Journal of Distributed Sensor Networks)
Ciphertext-policy attribute-based encryption is a promising mechanism with fine-grained access control for cloud storage system. However, there is a long-lasting problem of key abuse that a user may share its decryption key and a semi-honest authority may illegally issue decryption keys for unauthorized users for profits. To address this problem, we propose an accountable ciphertext-policy attribute-based encryption scheme. In our construction, there are two authorities to issue keys for users, but they cannot decrypt any ciphertexts without collusion. A shared key can be effectively traced, and if the traced identity claims that it is innocent, an auditor can publicly audit who will be responsible for the shared key. Compared with existing accountable ciphertext-policy attribute-based encryption schemes, the proposed scheme is more practical from the two aspects: (1) a user can normally request for a decryption key along with a short signature, and no additional interaction between users and authorities is needed; and (2) the complexity of tracing a masked secret key is reduced to | U | exponent computation, where | U | denotes the number of users in the system. At last, we give the security and experimental analysis.